2020
DOI: 10.1111/jorc.12324
|View full text |Cite
|
Sign up to set email alerts
|

Use of the esa resistance index to guide dosing for anaemia management

Abstract: SUMMARY Background Identifying erythropoiesis‐stimulating agent (ESA) resistance is important for treating reversible causes, reaching target haemoglobin levels with minimal dosing, avoiding adverse effects and reducing costs. The resistance index (RI, dose/kg weight/g haemoglobin/dl) is reportedly superior to absolute or weight‐based dosing. Objectives With the growing number of ESA classes and medications, our goal was to develop methodology to establish RI ranges in otherwise healthy haemodialysis patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…ESA dosing was examined as a proportion receiving a dose above the cohort median ( ), continuously, and by a resistance index that normalized for body weight and hemoglobin concentrations, as these two factors are strong determinants of ESA dosing. 8 We used the most recently available hemoglobin concentrations, typically measured once or twice monthly, and estimated body weight, adjudicated monthly by the nephrology team, from outpatient dialysis records prior to hospitalization. Additional characteristics were extracted by inpatient electronic medical record review [self-reported age, sex assigned at birth (male, female), race/ethnicity (white, black, Hispanic, other race)], outpatient dialysis record review [central venous catheter (CVC), arteriovenous fistula (AVF) or graft (AVG), total iron-binding capacity (TIBC)], participant interview [education ( grade, college or higher), tobacco history (past/present use, never)], and physical examination [edema (none, , )].…”
Section: Methodsmentioning
confidence: 99%
“…ESA dosing was examined as a proportion receiving a dose above the cohort median ( ), continuously, and by a resistance index that normalized for body weight and hemoglobin concentrations, as these two factors are strong determinants of ESA dosing. 8 We used the most recently available hemoglobin concentrations, typically measured once or twice monthly, and estimated body weight, adjudicated monthly by the nephrology team, from outpatient dialysis records prior to hospitalization. Additional characteristics were extracted by inpatient electronic medical record review [self-reported age, sex assigned at birth (male, female), race/ethnicity (white, black, Hispanic, other race)], outpatient dialysis record review [central venous catheter (CVC), arteriovenous fistula (AVF) or graft (AVG), total iron-binding capacity (TIBC)], participant interview [education ( grade, college or higher), tobacco history (past/present use, never)], and physical examination [edema (none, , )].…”
Section: Methodsmentioning
confidence: 99%
“…Dosing of ESA was examined at the maximum monthly recommended dosing per package guidelines (360 μg/mo or higher) 19 continuously and, because hemoglobin concentration and body weight are the major determinants of ESA dosing, by ESA resistance, which divides the mean monthly ESA dose by the product of mean monthly hemoglobin concentration and body weight (kilograms). 20 To limit extreme outliers, values were winsorized at the 99.5th percentile.…”
Section: Outcomementioning
confidence: 99%
“…However, household lead contamination is generally chronic and stable, the kidney failure population tends to be geographically constrained to their dialysis centers, and we included a sample size large enough to detect even underestimated associations. In addition, other sources of lead, such as lead paint, were not .12 2018 476 (20) 42 (25) 12 (24) 10 ( 26)…”
Section: Strengths and Limitationsmentioning
confidence: 99%